PENGARUH PLYOMETRIC TRAINING TERHADAP PENINGKATAN KEKUATAN OTOT - OTOT ANGGOTA GERAK BAWAH PADA ATLET : Literature Review - Ayu Puji Lestari, (2021)
Background : Increased muscle strength in athletes is something that is needed by an athlete. Plyometric Training is an exercise that can increase muscle strength in athletes, especially in the muscles of the lower limbs. Objective :The purpose of this study is to review increase strength lower body muscle strength in athlete. Methods: This literature study aims to review the literature, journals, articles, or research results on the topic of effect of plyometric training on lower body muscle strength in athlete . Methods Search for sources of literature, journals, articles, research results in several databases such as Google Scholar, Elsevier, and PubMed by using certain keywords in the period 2017-2020. From the literature search results, 12 articles were obtained and only 7 articles met the source inclusion criteria. The methodological quality assessment of 7 articles was assessed using the Scimago Journal & Country Rank (SJR). Result :Analysis of 7 journals was carried out based on the suitability of the topic, the research methods used, samples, interventions, instruments / parameters, and the results of each article. Results After reviewing the literature as many as 7 articles showed that plyometric training can increase lower body muscle strength in athlete. Conclusion : Conclusion plyometric training can increase lower body muscle strength in athlete Keywords : Plyometric training, Strength, Lower limb